Pengaruh Campuran Bahan Bakar Biodiesel WCO - Diesel terhadap Karakteristik Api Hasil Pembakaran Spray Difusi pada Concentric Jet Burner - Sukri, Sukri; Sasongko, Mega Nur; Widodo, Teguh Dwi (Jurnal Rekayasa Mesin, 2021)
Biofuels from waste cooking oil (WCO) represent a sizable opportunity not only in terms of energy production but also as a way for sustainable development despite their low yield, higher viscosity, lengthy production time and cost. Alternatively, biodiesel can be blended at an appropriate blending ratio with convention diesel oils. The biodiesel and its blends is proved to give better emission characteristics than conventional diesel oils. This study aims to experimentally investigate the effect of the fuel blend on the combustion characteristics of Â WCO biodiesel. The characteristic are the droplet size, flame height, flame width and temperature distribution. In this study, the blended fuel are B0 (Solar), B10, B20, B30, B40 and B100 (WCO biodiesel). Measurement and visualization of the combustion flame for each variation of the fuel mixture was were tested at different pressures, namely 4 bar and 5 bar. The experimental results show that the droplet size increases with increasing WCO concentration in the fuel; on the other hand, visualization and calculations show that the height and width of the flame of the fuel mixture decreases Observation on the temperature distribution shows that the WCO biodiesel mixture has the potential to increase the fire temperature at certain points